How do they decide? Performance support staff perceptions of decision-making in elite-sport environments - Wilson, P. J.; Roe, G.; Kiely, J. (The Journal of Strength and Conditioning Research, 2025)
Decision-making is a critical component of performance support staff responsibilities, yet research exploring staff perceptions relating to key facets of decision-making is lacking. This study aimed to explore perceptions of performance support staff relating to; the importance of decision-making in their role, the value of team decision-making, strategies to enhance decision-making skills, monitoring the process and outcome of decisions, and the obstacles to good decision-making within their professional contexts. A mixed-methods approached was used to explore perceptions of decision-making in 191 performance support staff (male staff = 179, female staff = 12) working in professional (n = 147) or international (n = 44) sport. Performance support staff reported decision-making as extremely important to their role; however, only 31% had received formal decision-making education and revealed underdeveloped decision-making capabilities within their organizations as a barrier to good decision-making. Most performance support staff conveyed that team decision-making is a valuable endeavor and augments decision outcomes; yet articulated dysfunctional team dynamics as an obstacle to good decision-making in their environments. Largely, performance support staff reported an absence of organizational strategy and workflow systems and processes for tracking and making decisions, respectively, whereas only 22% had a consistent reviewing and updating process. When making decisions, performance support staff faced several different cognitive biases and were challenged by the environmental pressures. The perspectives documented here suggest that performance support staff would likely benefit from undertaking evidence-based training and implementing scientifically informed strategies to enhance decision-making processes within their organizations.